1990
DOI: 10.1111/j.1439-0264.1990.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Zum Wachstum von Skelett, Körpermasse und Muskelfaserdurchmesser der Pute (Meleagris gallopavo) vom Schlupf bis zum 224. Lebenstag

Abstract: Growth of body mass, femur, tibiotarsus, and tarsometatarsus length as well as the diameter of muscle fibers in the M. pectoralis were measured in (Large White) female turkeys between birth and day 224. Growth-specific approximations were established with the Janoschek function as modified by Sager (1978) and with the Logistic function. While the Janoschek function fairly described the growth of the turkey, the Logistic function throughout gave beginning values that were too high and theoretical end values tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Both fiber types showed a sigmoid growth pattern, a pattern frequently found for growth processes in higher vertebrates and previously reported for FTG fiber growth in turkeys (Anger, 1987;Salomon et al, 1990). One advantage of the Janoschek growth curve is that its point of inflection is optional and highly flexible (for details see Gille and Salomon, 1995a).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Both fiber types showed a sigmoid growth pattern, a pattern frequently found for growth processes in higher vertebrates and previously reported for FTG fiber growth in turkeys (Anger, 1987;Salomon et al, 1990). One advantage of the Janoschek growth curve is that its point of inflection is optional and highly flexible (for details see Gille and Salomon, 1995a).…”
Section: Discussionsupporting
confidence: 64%
“…The fiber composition of the M. pectoralis in birds shows close relationships to the mode of flight. In birds performing short bursting flights, as in many Galliformes, this muscle is almost exclusively composed of FTG fibers (Ashmore and Doerr, 1971;Salomon et al, 1990;Ono et al, 1993;Smith et al, 1993). On the contrary, the M. pectoralis of most birds exhibit-ing sustained flapping flights only contains FTO fibers, which allow almost as powerful contractions as FTG fibers but are more fatigue resistant (Caldow and Furness, 1993;Rosser et al, 1994).…”
mentioning
confidence: 99%
“…By using the Janoschek functions. Salomon et al (1988Salomon et al ( , 1990 found analogous results with 0.352, 0.394, 0.414 and 0.303 (y + /A) and 52.3, 74.4, 27.6 and 24.3 d (t + ) for chickens, turkeys, ducks and geese, respectively.…”
Section: Growth Patternmentioning
confidence: 71%
“…Some comparisons of growth, fat deposition and efficiency of meat production in domestic birds, ie chickens and turkeys ( Galliforms), ducks and geese (Anseriforms), have been presented by Nixey (1986) and Shalev and Pasternak (1989). Further comparative analyses of the growth patterns in poultry were carried out by Salomon et al (1988Salomon et al ( , 1990 and Anthony et al (1991).…”
Section: Introductionmentioning
confidence: 99%
“…Further comparative analyses of the growth patterns in poultry were carried out by Salomon et al (1988Salomon et al ( , 1990 and Anthony et al (1991).…”
mentioning
confidence: 99%